Developing Reading Competence Through An Eclectic Approach In Teaching English - Mamedova Farangis Mirmusoevna (Zien Journals, 2025)
The article provides information about the advantages of the eclectic approach. The importance of the innovative approach is illustrated through clusters and supported by theoretical data.
Keywords: Eclectic method; innovative approach; eclecticism